Survey of Skills Sets for the Implementation Building Information Modeling in Construction Education Body of Knowledge in Nigeria - Hammad, D.B. (Institute of Electrical and Electronics Engineers Inc., 2020)
The Construction industry globally is transforming significantly due to the emergence and development of Information and Communication Technology. One of the significant impacts of information technology in the construction industry is the emergence of Building Information Modeling. Building information modeling will ameliorate the defragmented nature of the construction industry and subsequently improves productivity. Despite the great importance of this technology globally, there is little effort to study how to implement the technology in the construction educational body of knowledge in Nigeria. On this premise, the study sought to evaluate the skill sets required to implement Building Information Modelling in the Nigerian Construction Industry. The study uses a survey research design. A total of 375 experts were randomly selected for the study, and 233 were used for the analysis. A Cronbach alpha of.916 was obtained, and the Kruskal-Wallis statistical tool was used to find the differences from the five primary attributes of the construction body of knowledge. The results indicated no significant differences in responses among the experts on the importance of all the five variables in relation to the respondents' sector. Â© 2020 IEEE.